Congenital chikungunya infection and neurodevelopmental outcomes at 18 months follow up- A case series from North India - Bichitrananda Raut; Susanta Kumar Badatya; Sweta Kumari; Neelam Kler; Pankaj Garg; Anup Thakur (Wolters Kluwer Medknow Publications, 2019)
Introduction : Early and late neurologic complications of congenital chikungunya fever has been underreported in published literature. We describe the acute clinical manifestations and long term neurodevelopmental outcomes of congenital chikungunya in a recent case series. Objective: To describe clinical manifestations of congenital chikungunya and its neurodevelopmental outcomes at 18 months follow up. Methods : Medical records of the neonates born to mothers with chikungunya admitted in Sir Gangaram Hospital, New Delhi during August to November 2016 were reviewed. All exposed neonates were observed for signs and symptoms of chikungunya and managed as per departmental protocol. Newborns with positive cord blood or postnatal RT-PCR were defined to have congenital chikungunya. These infants were evaluated for developmental disabilities at 18 months of age by ages and stages questionnaire (ASQ-3). Results: Seventeen neonates were considered to be "exposed" being delivered to chikungunya positive mothers. Of them, nine (52.9%) were labelled as infected on basis of positive cord blood RT-PCR. Eight neonates became symptomatic with development of typical chikungunya rash in 6 (66.6%), fever in 5 (55.5%), encephalopathy in 8 (100%), and seizure in 4(50%) neonates with one mortality(11%). MRI-brain was abnormal in six encephalopathic (75%) neonates. Based on parental response of ASQ-3 questionnaire, neurodevelopment was learnt to be normal in six infants (75%) and two (25%) had delay in motor and communication skills. Conclusion: Although few babies developed developmental delay, significant proportion of them recovered by 18 months of age inspite of severe neurotropic manifestation of congenital chikungunya.